2022
DOI: 10.1111/ajt.16842
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo generation of regulatory T cells from liver transplant recipients using costimulation blockade

Abstract: The potential of adoptive cell therapy with regulatory T cells (Tregs) to promote transplant tolerance is under active exploration. However, the impact of specific transplant settings and protocols on Treg manufacturing is not well‐delineated. Here, we compared the use of peripheral blood mononuclear cells (PBMCs) from patients before or after liver transplantation to the use of healthy control PBMCs to determine their suitability for Treg manufacture using ex vivo costimulatory blockade with belatacept. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(254 reference statements)
0
3
0
Order By: Relevance
“…A platform has been developed for solid organ transplant in which allo(donor)-specific Tregs from healthy donors or recipients post-transplantation are expanded in the presence of co-stimulatory blockade. Such Tregs maintain Foxp3 demethylation status which strongly correlates with stability ( 181 , 182 ).…”
Section: Enhancing Ex Vivo Treg Expansion and Stabilitymentioning
confidence: 99%
“…A platform has been developed for solid organ transplant in which allo(donor)-specific Tregs from healthy donors or recipients post-transplantation are expanded in the presence of co-stimulatory blockade. Such Tregs maintain Foxp3 demethylation status which strongly correlates with stability ( 181 , 182 ).…”
Section: Enhancing Ex Vivo Treg Expansion and Stabilitymentioning
confidence: 99%
“…Studies have also shown that costimulatory pathways blockade could limit the activation of T cells reversely ( 12 ), which may alter the immune response against allograft and attenuate rejection, prolonging graft survival time ( 13 ). Currently, the potential for adoptive cell therapy with Tregs to promote transplant tolerance is being actively explored ( 14 ). Although most results of these trials are optimistic, many experimental and clinical unanswered questions are slowing the progression of this new therapeutic alternative ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…End-stage renal disease is also more permissive than end stage liver disease of harsh conditioning regimens that underpin some tolerance protocols. 8 Delayed protocols for immunosuppression withdrawal that do not involve intense conditioning are being developed, particularly in liver, 9 and as the practice of tolerance advances, it is important to keep in mind the pediatric liver transplant population.…”
mentioning
confidence: 99%